1992
DOI: 10.3382/ps.0710188
|View full text |Cite
|
Sign up to set email alerts
|

Chlorination of Poultry Chiller Water: Chlorine Demand and Disinfection Efficiency

Abstract: A study was conducted to determine the general composition of equilibrated poultry chiller water (near maximum solids content) from a commercial operation, the chlorine consumption by its components, and the chlorine dosage necessary to achieve its disinfection. The equilibrated chiller water contained .35% (CV, 40%) solids, which consisted of lipids (56%), ash (33%), and total nitrogen (4.2%). Residual chlorine and survival of aerobic bacteria were determined in chiller water dosed with chlorine levels rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 12 publications
0
48
0
1
Order By: Relevance
“…Similar findings were reported by Lin, Huang, Cornell, Lin, and Wei, 1996, who observed that L. monocytogenes washed off the fish cubes at high-level inoculation was not completely eliminated by the three chlorinating solutions used (aqueous chlorine, chlorine dioxide obtained in situ and commercial chlorine dioxide), even at 400 ppm. Tsai, Schade, and Molineux, 1992 showed that poultry chlorinating chiller water at 40 mg/l of chlorine reduced L. monocytogenes in poultry by only 37-50% in 3-5 min. At least 100 mg/l of chlorine was needed in order to achieve a 99% (two log units) reduction.…”
Section: Inactivation Of L Monocytogenes By Chlorinating Solutionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar findings were reported by Lin, Huang, Cornell, Lin, and Wei, 1996, who observed that L. monocytogenes washed off the fish cubes at high-level inoculation was not completely eliminated by the three chlorinating solutions used (aqueous chlorine, chlorine dioxide obtained in situ and commercial chlorine dioxide), even at 400 ppm. Tsai, Schade, and Molineux, 1992 showed that poultry chlorinating chiller water at 40 mg/l of chlorine reduced L. monocytogenes in poultry by only 37-50% in 3-5 min. At least 100 mg/l of chlorine was needed in order to achieve a 99% (two log units) reduction.…”
Section: Inactivation Of L Monocytogenes By Chlorinating Solutionsmentioning
confidence: 98%
“…Chlorine demand is affected by factors such as the presence of organic compounds and interactions between such compounds and chlorine. The competition for available chlorine between bacterial constituents and chicken components affects bactericidal activity (Tsai et al, 1992).…”
Section: Inactivation Of L Monocytogenes By Chlorinating Solutionsmentioning
confidence: 99%
“…Organic material in the chiller water q: From Tsai et al (1992), the total suspended solids in the chiller water is 0.35% (i.e. about 3500 mg/l) (this value is similar to the initial measuring station in the tank (Northcutt et al, 2008)).…”
Section: Parameters Specific To Canadian Processingmentioning
confidence: 99%
“…Due to the fact that the we have a relatively complete data set for generic E. coli, both bacteria levels and transfer during industrial chiller processes (Cavani, Schocken-Iturrino, Garcia, & de Oliveira, 2010;Northcutt, Smith, Huezo, & Ingram, 2008;Tsai, Schade, & Molyneux, 1992) and chlorine inactivation (Helbling & VanBriesen, 2007), we tailor our model to address the specific dynamics associated to the chiller water chemistry and cross-contamination of broiler carcasses contaminated with non-pathogenic E. coli. For the parameter ranges specific to this situation, the solutions of system (7) approach S on the order of 200e250 min, which means during a typical 8 h shift, if there is little variation in the average E. coli load on carcasses, i.e.…”
Section: Model Propertiesmentioning
confidence: 99%
“…These technologies involve the use of chlorine, chlorine dioxide, Salimide, ozone, and cetylpyridinium chloride [5][6][7][8][9].…”
Section: Chemical Informatics Issn 2470-6973mentioning
confidence: 99%